Review of the Aeolothripidae (Thysanoptera) in Japan - Masumoto, Masami; Okajima, Shûji (Zootaxa, 2019)
Japanese Aeolothripidae are reviewed, with three genera and 10 species recognized including the following four new species: Aeolothrips fukusimensis sp. n., A. setosus sp. n., Desmidothrips japonicus sp. n. and Franklinothrips oblongus sp. n. One species, A. gloriosus, is excluded from the Japanese fauna. Moreover, A. kurosawai is newly recorded from Taiwan and A. luteolus is newly recorded from Korea.